Targeted inhibition of long non-coding RNA H19 blocks anaplastic thyroid carcinoma growth and metastasis. Issue 1 (1st January 2019) - Zhang, Honglai; Yu, Ying; Zhang, Kejun; Liu, Xinfeng; Dai, Yan; Jiao, Xuelong
ABSTRACT: Long non-coding RNA H19 (H19) is highly expressed in cancers and is considered to highly correlate with the extent of malignant degree. The present study was performed to determine the expression levels of H19 in anaplastic thyroid carcinoma (ATC) tissues and the role of H19 in ATC 8505C cells in vitro and in vivo . Expression of H19 was detected in 19 ATC and 19 normal thyroid tissues by real-time quantitative polymerase chain reaction. Utilizing the siRNA or short hairpin RNA (shRNA) directed against human H19 (H19 siRNA or shRNA H19) depleted H19 in ATC 8505C cells and characterized the outcomes. The results showed that H19 was overexpressed in ATC tissues. Targeting H19 inhibited proliferation, migration, and invasion and induced apoptosis in 8505C cells in vitro and inhibited tumorigenesis and metastasis in vivo . Therefore, the H19 might be an effective target for ATC molecular therapy. Graphical Abstract: uf0001